Efficacy and tolerability of perampanel: a Chinese real-world observational study in epilepsy - Zeng, Ya; Wu, Xintong (Frontiers in Neurology, 2024)
Purpose To investigate whether there exists a statistically significant distinction between the effectiveness and tolerance of perampanel (PER) and the number of antiseizure medications (ASMs) that were tried prior to administering PER. Method A prospective, observational study was performed at West China Hospital of Sichuan University. The study included patients diagnosed with epilepsy who were prescribed PER and were monitored for a minimum of 6 months. The efficacy of PER was evaluated at 1, 3, 6, and 12-month intervals by examining the retention rate and the 50% response rate. All statistical analyses were conducted using IBM SPSS Statistics version 25 (IBM Corporation, Armonk, New York). Results A total of 1,025 patients were identified, of which 836 were included in the analysis. Seven hundred and eighty-nine patients (94.4%) were followed up for a year. The median age of the patients was 29.32 ± 14.06 years, with 45.81% of the patients being male and 17.0% being adolescents. The average duration of epilepsy was 11.22 ± 8.93 years. Overall, PER was discontinued in 49.5% of patients, with the most common reasons being inadequate therapeutic effect and treatment-emergent adverse events (TEAEs). At the 6-month follow-up, the retention rate was 54.2% (454/836), and 39.6% of patients had a 50% response. At the 12-month follow-up, the retention rate was 49.4% (340/789), and 44.5% of patients had a 50% response. Patients who received PER as monotherapy had the highest retention rates (P = 0.034) and 50% response rates (P < 0.001) at any follow-up point. TEAEs were reported in 32.0% of patients, and these led to discontinuation in 15.4% of patients. The most common TEAEs were dizziness and somnolence. There was no significant difference between subgroups (P = 0.57), but there was a significant difference between the dosage of PER and TEAEs (P < 0.001). Main findings The study concludes that PER is effective in treating both focal and generalized tonic-clonic seizures. Patients who had fewer previous exposures to ASMs exhibited higher response rates to PER. TEAEs related to PER dosage were more prevalent during the first 3 months of treatment and tended to improve with continued use, ultimately demonstrating favorable long-term tolerability.